2020
DOI: 10.2147/lra.s181459
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emergence Agitation and Delirium: Considerations for Epidemiology and Routine Monitoring in Pediatric Patients</p>

Abstract: Emergence from anesthesia can be associated with a wide spectrum of cognitive and behavioral dysregulation in children, including delirium or acute brain dysfunction. This period of neurobehavioral recovery can be further confounded by pain, anxiety, and fear. The implementation of monitoring for level of consciousness, pain, and delirium using valid pediatric tools is necessary to avoid misdiagnosis due to overlapping symptomatology and support appropriate management. Understanding the epidemiology of deliriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 77 publications
0
46
0
Order By: Relevance
“…Accumulating evidence has shown that EA/delirium has a strong relationship with POD ( Sharma et al, 2005 ; Neufeld et al, 2013 ; Card et al, 2015 ). However, distinguishing EA from emergence delirium is still challenging ( Kwak, 2010 ; Lee and Sung, 2020 ; Menser and Smith, 2020 ). Pediatric EA appears to be an asynchronism of different brain regions during the washout of volatile anesthetics and tends toward anxiety due to immature psychology ( Dahmani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that EA/delirium has a strong relationship with POD ( Sharma et al, 2005 ; Neufeld et al, 2013 ; Card et al, 2015 ). However, distinguishing EA from emergence delirium is still challenging ( Kwak, 2010 ; Lee and Sung, 2020 ; Menser and Smith, 2020 ). Pediatric EA appears to be an asynchronism of different brain regions during the washout of volatile anesthetics and tends toward anxiety due to immature psychology ( Dahmani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric EA has attracted widespread attention due to its high incidence ( Voepel-Lewis et al, 2003 ; Silva et al, 2008 ; Kanaya, 2016 ; Menser and Smith, 2020 ). In recent years, adult EA has been the top priority of perioperative management ( Lepousé et al, 2006 ; Lee and Sung, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This dissociated state of consciousness has been referred to by various terms since it was first described, including emergence agitation (EA), emergence delirium (ED), and emergence excitation. Although these terms are not synonymous with each other, they have been used interchangeably to describe behavioral dysregulation in the post‐anesthesia period, particularly in pediatric patients 2 …”
Section: Introductionmentioning
confidence: 99%
“…Currently, the mechanism behind EA/ED remains unclear. As there are no validated methods for the prevention or treatment of EA/ED, various efforts are ongoing to identify the risk factors for and reduce the incidence and severity of EA/ED 2 . One suggested pharmacologic intervention for the prevention of EA/ED is the intraoperative administration of magnesium sulfate 5 …”
Section: Introductionmentioning
confidence: 99%
“…Dexmedetomidine (Dex) is currently widely used in critically ill patients, with ideal sedative and analgesic effects, and can be used as one of the adjuvant clinical anesthesia drugs [6] . Clinical studies have confirmed that dexmedetomidine plays an important role in resisting inflammatory response and protecting organs [7] . However, the mechanism of the anti-inflammatory effect of dex and sepsis induced acute lung injury is not clear, so the purpose of this study is to explore the effect of DEX on alveolar lavage fluid inflammatory factor and MAPK-related signaling pathway in mice with acute lung injury induced by lipopolysaccharide (LPS).…”
mentioning
confidence: 96%